Interferon Lambda 3/4 (IFNλ3/4) rs12979860 Polymorphisms Is Not Associated With Susceptibility to Systemic Lupus Erythematosus, Although It Regulates OASL Expression in Patients With SLE - Juárez-Vicuña, Yaneli; Pérez-Ramos, Julia; Adalid-Peralta, Laura; Sánchez, Fausto; Martínez-Martínez, Laura Aline; Ortiz-Segura, María del Carmen; Pichardo-Ontiveros, Edgar; Hernández-Díazcouder, Adrián; Amezcua-Guerra, Luis M.; Ramírez-Bello, Julian; Sánchez-Muñoz, Fausto (Frontiers in Genetics, 2021)
Systemic lupus erythematosus (SLE) is an autoimmune disease with a complex etiology. Various genetic factors are associated with susceptibility to developing SLE and contribute to its onset and progression. Different single-nucleotide polymorphisms (SNPs) have been associated with SLE in several populations. The rs12979860 SNP in interferon lambda 3/4 (IFNλ3/4) is significantly associated with SLE susceptibility in patients negative for nephritis in Taiwanese people, and interferon-stimulated genes (ISGs) are differentially expressed in normal liver by the rs12979860 genotype. This study aimed to investigate whether rs12979860 is associated with the presence of SLE and lupus nephritis in Mexican individuals as well as with the expression of several ISGs in SLE patients. In total, 439 SLE patients and 358 healthy donors were genotyped for rs12979860 using real-time PCR, and allelic discrimination plots were constructed. Additionally, peripheral blood mononuclear cells (PBMCs) were isolated from the venous blood of SLE patients by centrifugation (n=78). The mRNA levels of 2'-5'-oligoadenylate synthetase like (OASL), myxovirus resistance 1 (MX1), 2'5'-oligoadenylate synthetase 1 (OAS1), interferon-stimulated gene 15 (ISG15) and lymphocyte antigen 6 complex, locus E (LY6E) were determined using real-time PCR. The distributions of rs12979860 genotypes and allele frequencies were compared between SLE patients and healthy donors; case-control analysis revealed that rs12979860 was not associated with SLE susceptibility (OR 1.18, 95% CI 0.97–1.45, p=0.08) or with the risk for lupus nephritis (OR 0.913, 95% CI 0.590–1.411, p= 0.682). However, OASL expression levels in PBMCs were significantly different between rs12979860 genotypes in SLE patients: median OASL-1 mRNA levels were significantly higher in patients carrying the CC genotype (197.10, IQR 71.10–411.17) than in those with CT/TT genotypes (173.75, IQR 58.80–278.75, p=0.016). Our results suggest that the SNP rs12979860 does not play a relevant role in susceptibility to SLE in Mexican individuals. However, IFNλ3/4 genotypes appear to be associated with OASL expression in PBMCs from patients with SLE.